The Effect Of Nurse Caring and Complain Handling On The Intention Of Revisits With Trust Mediation: Anna Medika Hospital Study (Jurnal Health Sains, 2022)
Along with the rapid development of the industrial revolution era, the progress of health services certainly needs to be considered. It aims to be able to meet the patient's need for excellent service from the hospital. Hospitals are required to continue to develop appropriate strategies to retain their customers, namely by conducting nursing care coaching, paying attention to incoming complaints so that it will foster trust and the intention of repeat patient visits in the future. This study aims to analyze the effect of caring for nurses and handling complaints on intention to revisit at Anna Medika Hospital mediated by trust. This study uses a quantitative method of causality. The population in this study were all patients who had visited the outpatient unit of Anna Medika Hospital, with a purposive sampling method of 200 respondents. The data analysis method used is SEM-LISREL to test the effect of the relationship between research variables and test the research hypothesis. The results showed that: There is a positive and significant effect of nurse caring and complaint handling on trust and intention to revisit and trust partially mediates the effect of nurse caring and complaint handling on revisit intentions. These results have implications for nursing and marketing managers to actively participate in improving the nurse caring system, complaint management system and marketing system